2021
DOI: 10.1186/s12888-021-03198-y
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical pattern of Kessler psychological distress distribution in the general population of the U.S. and Japan

Abstract: Background Although the 6-item Kessler psychological scale (K6) is a useful depression screening scale in clinical settings and epidemiological surveys, little is known about the distribution model of the K6 score in the general population. Using four major national survey datasets from the United States and Japan, we explored the mathematical pattern of the K6 distributions in the general population. Methods We analyzed four datasets from the Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…According to the K6 scores, the adjusted prevalence of SMI among workers in veterinary clinics, 11.1%, and that of veterinary nurses, 14.9%, were high compared with the global prevalence of depression before COVID-19, 4.4% [ 38 ]. The prevalence of SMI K6 cutoff 12/13 among Japanese citizens in 2016 was reported to be 3.9% [ 34 ]. The respondents in the present study are only from a working population, while the global and Japanese prevalences of SMI [ 34 , 38 ] included those not working due to SMI; the results suggested that workers in companion animal clinics are distressed at higher levels than in the general population before COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the K6 scores, the adjusted prevalence of SMI among workers in veterinary clinics, 11.1%, and that of veterinary nurses, 14.9%, were high compared with the global prevalence of depression before COVID-19, 4.4% [ 38 ]. The prevalence of SMI K6 cutoff 12/13 among Japanese citizens in 2016 was reported to be 3.9% [ 34 ]. The respondents in the present study are only from a working population, while the global and Japanese prevalences of SMI [ 34 , 38 ] included those not working due to SMI; the results suggested that workers in companion animal clinics are distressed at higher levels than in the general population before COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of SMI K6 cutoff 12/13 among Japanese citizens in 2016 was reported to be 3.9% [ 34 ]. The respondents in the present study are only from a working population, while the global and Japanese prevalences of SMI [ 34 , 38 ] included those not working due to SMI; the results suggested that workers in companion animal clinics are distressed at higher levels than in the general population before COVID-19 pandemic. A high proportion (9%) of 30–39-year-old veterinarians with serious psychological distress was reported in 2015 from the United States of America [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, K6-scores show a right skew ( Tomitaka et al, 2019 ) across different age groups; both in adolescent ( Green et al, 2010 ; Peiper et al, 2014 ) and adult samples ( Kang et al, 2015 ; Tomitaka and Furukawa, 2021 ). The majority of respondents report minimal or minor psychological distress (K6 score up to 4).…”
Section: Methodsmentioning
confidence: 97%
“…Each item is rated on a scale of 0 to 4, with the total score ranging from 0 to 24; the higher the score, the greater the psychological distress. It is an excellent screening tool for mood and anxiety disorders [ 22 , 23 ], and the validity of the Japanese version has been confirmed [ 24 ].…”
Section: Methodsmentioning
confidence: 99%